The effects of an acute bout of ergometer cycling on young adults' executive function: A systematic review and meta-analysis - Tamara S. Dkaidek; David P. Broadbent; Daniel T. Bishop (Elsevier, 2023)
Purpose: The extent to which acute exercise improves executive function (EF) remains indeterminate. The purpose of this systematic review and meta-analysis was to determine the effect of acute ergometer cycling exercise on executive function (EF), including the potential moderating effects of exercise intensity and duration, EF task type, and EF task onset. Methods: We searched seven electronic research databases using cycling- and cognition-related terms. All 17 studies included were published in the last 10 years and comprised healthy participants aged 18-35 years who completed tasks assessing a variety of EFs before and after cycling exercise lasting 10-60 min. We analyzed 293 effect sizes obtained from 494 individuals (mean age = 22.07 ± 2.46 yrs). Additional analyses were performed, using averaged effect sizes for each separate study to examine the omnibus effect across studies. Results: There was a positive effect of acute ergometer cycling exercise on response time (RT) in 16 of 17 studies reviewed and a positive effect for response accuracy (RA) in 8 of 14 studies; three studies did not report RA data. Hedges' g effect sizes [95% CI] for RT ranged from 0.06 [-0.45, 0.56] to 1.50 [0.58, 2.43] and for RA from −1.94 [-2.61, −1.28] to 1.03 [0.88, 1.19].Bouts of cycling completed at moderate intensities appear to have the greatest effect on RT (Hedges' g = 1.03 [0.88, 1.19]) but no significant effect on RA; bouts with durations of 21-30 min appear to offer the greatest benefits for both RT (Hedges' g = 0.77 [0.41, 1.13]) and RA (Hedges' g = 0.92 [0.31, 1.52]). Effect sizes were greatest for RT in inhibitory control tasks (Hedges' g = 0.91 [0.80, 1.03]) and for RT when EF tasks were completed immediately post-exercise (Hedges' g = 1.11 [0.88, 1.33]). Findings were similar in the omnibus analyses: moderate-intensity bouts had the greatest effect on RT, SMD = 0.79 (95% CI [0.49, 1.08]), z = 5.20, p < 0.0001, as did cycling durations of 21-30 min, SMD = 0.87 (95% CI [0.58, 1.15], z = 5.95, p < 0.0001. The greatest benefits were derived for inhibitory control tasks, SMD = 0.70 (95% CI [0.43, 0.98]), z = 5.07, p < 0.04, and when the EF task was completed immediately post-exercise, SMD = 0.96 (95% CI [0.51, 1.41]), z = 4.19, p < 0.001. There were no overall effects on RA. Conclusion: Our findings indicate that acute bouts of cycling exercise may be a viable means to enhance RTs in immediately subsequent EF task performance, but moderating and interactive effects of several exercise parameters must also be considered.